2002
DOI: 10.1074/jbc.m110188200
|View full text |Cite
|
Sign up to set email alerts
|

Endosomal Proteolysis of Internalized Insulin at the C-terminal Region of the B Chain by Cathepsin D

Abstract: The endosomal compartment of hepatic parenchymal cells contains an acidic endopeptidase, endosomal acidic insulinase, which hydrolyzes internalized insulin and generates the major primary end product A 1-21 -B 1-24 insulin resulting from a major cleavage at residues Phe B24 -Phe B25 . This study addresses the nature of the relevant endopeptidase activity in rat liver that is responsible for most receptor-mediated insulin degradation in vivo. The endosomal activity was shown to be aspartic acid protease catheps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 64 publications
(114 reference statements)
9
77
1
Order By: Relevance
“…This is consistent with there being some constitutive release of insulin as well as degradation of insulin by the liver cells. 16,17 Neither of these features occurs in a pancreatic b cell, but insulin degradation does occur in a normal liver cell. Constitutive release is not a feature of a pancreatic b cell, but a small amount of insulin is degraded in these cells, within the secretory granules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with there being some constitutive release of insulin as well as degradation of insulin by the liver cells. 16,17 Neither of these features occurs in a pancreatic b cell, but insulin degradation does occur in a normal liver cell. Constitutive release is not a feature of a pancreatic b cell, but a small amount of insulin is degraded in these cells, within the secretory granules.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison the amount of insulin degraded by NIH 3T3 cells (negative control) was negligible. It has been known for some time that the endosomal compartment of hepatocytes contains an acidic endopeptidase or endosomal acidic insulinase, which has recently been confirmed to be cathepsin D. 17 The activity of cathepsin D is almost completely inactivated by protease inhibitors, such as pepstatin A. 17,18 We incubated Huh7 cells over a 24-h period in DMEM medium and a 6-h period in basal medium, in the presence of pepstatin A, and confirmed that insulin degradation was negligible in the presence of the protease inhibitor.…”
Section: Insulin Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…To reset the system, the inactive insulin is separated from the receptor, and the receptor is either recycled to the cell surface or degraded in the cytosol. In the meantime, insulin is degraded by IDE in the endosome [106], [107] and then completely digested into amino acids by lysosomal peptidases. If insulin is incompletely degraded in the cytosol, insulin peptide fragments in the cytosol can interfere with insulin-mediated signal transduction mechanisms resulting in insulin resistance and diabetes.…”
Section: Methods Of Treating Alzheimer's Disease and Type 2 Diabetesmentioning
confidence: 99%
“…Polyclonal antibody against growth factor receptor-bound protein 14 (GRB14) has been previously described [15]. Rabbit antimouse cathepsin D R291 [16,17], sheep anti-human cathepsin D M8147 [16,17] and rabbit anti-rat cathepsin B 7183 [18] were obtained from J. S. Mort (Shriners Hospital for Crippled Children, Montreal, Canada). Monoclonal antibody directed against insulin-degrading enzyme (IDE) [19,20] was obtained from R. A. Roth (Stanford University, Stanford, CA, USA).…”
Section: Methodsmentioning
confidence: 99%